Negotiating Minority Identities in Europe Through Cultural Preservation: Music as Heritage among the Dutch Hindustani Diaspora in the Netherlands - Sengupta, Roshni (Journal of intercultural studies, 2024)
Twice-migrant and descended from the colonial labour diaspora, the Dutch Hindustanis in the Netherlands are one of the most assimilated, socially integrated and upwardly mobile minority diaspora groups in the Netherlands. The group also remains the repository of the early vestiges of Hindi film music as well as traditional music from the Northern Indian plains, thereby making it a fascinating case study for cultural preservation. This paper undertakes to take a close look at the modes and methods employed by the Dutch Hindustanis to preserve their musical heritage and argues that it has emerged as one of the primary nodes of diasporic identity formation for the group.